Endoscopic Versus Surgical Management and Outcome of CBD Stones 2020 - Balla, Talal Salah; Musaad, Abdulmagid Mohammed; alhaboob, Nassir; altayeb, Abdelmoneim (Gezira Journal of Health Sciences, 2021)
Background: Common bile duct stones are present in approximately 5% of the patients undergoing elective cholecystectomy and 10% of patients with acute cholecystitis with different modality of treatment. This study investigated  edoscopic and surgical management and outcome  of CBD stones among Sudanese patients at Ibn Sina Hospital October 2018 to October 2019. The study included 68 patients. Data was collected using a constructed structured pretest questionnaire. Objectives: To asses the outcome of endoscopic versus surgical management of common  Bile duct stones. Methods and patients: This is a hospital based descriptive cross-sectional study, which was conducted in Ibn Sena Specialized Hospital over a period of one year October 2018 to October 2019 . Results: 68 patients involved in the study , male to female ratio 0.6:1,the mean age was 61.2 years , patients underwent surgical management were 51.5%, patients underwent endoscopic management were 48.5%,multiple stones  found in 73.5%,single stone found in 26.5%,stone found to be more than 1 cm in 41.2% less than 1cm in 58.8%,the success rate in achieving bile duct clearance in surgical group was 100% and in endoscopic group was 75.7%,complications developed in surgical group was wound infection in 2.85%,complications developed in endoscopic group was cholangitis  9%,in adequate clearance with stenting 9%and failure of Ercp in 15.1%,prolonged hospital stay in surgical group in   comparison to endoscopic group                                                 . Conclusion: Surgical interventions were superior in achieving bile duct clearance there was significant correlation between size and number of stones and endoscopic failure and management.